A cytotoxic rabbit T-cell line infected with a gamma-herpes virus which expresses CD8 and class II antigens. - Wilkinson, J; Galea-Lauri, J; Reid, H (1992)
A rabbit T-cell line, BJ-610, has been derived from a New Zealand White rabbit infected with Alcelaphine herpes virus-1, which has the characteristics of a lymphokine activated killer (LAK) cell. The surface phenotype of this cell line has been studied by flow cytometry, using a panel of monoclonal antibodies (mAb) to rabbit leucocyte surface markers, and compared with that of another rabbit T-cell line, RL-5, transformed with herpes virus ateles. The expression of a number of markers is common to the two lines; these include the rabbit analogues of CD11a/CD18, CD43, CD44 and CD45. Three antigens are expressed on BJ-610 but not RL-5. One of these is recognized by a mAb thought to recognize CD8, while a second is a class II R-DQ molecule. The third antigen is expressed on thymocytes, a subset of T cells, neutrophils and platelets but its molecular nature is unknown. These two cell lines should prove useful in preparing reagents which recognize subsets of rabbit T cells and for studying the mechanism of herpes virus-induced lymphoid cell deregulation.